1992
DOI: 10.1093/bja/68.5.529
|View full text |Cite
|
Sign up to set email alerts
|

Esmolol Hydrochloride for Management of the Cardiovascular Stress Responses to Laryngoscopy and Tracheal Intubation

Abstract: In a double-blind, randomized, controlled prospective study, 30 grade ASA I/II patients received a continuous i.v. infusion of normal saline or esmolol hydrochloride before induction of anaesthesia and tracheal intubation. Arterial pressure and heart rate were measured to assess the pressor response to laryngoscopy and intubation. The heart rate decreased in the esmolol group before induction of anaesthesia. The pressor response to laryngoscopy was significantly less marked in the esmolol group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 5 publications
3
50
0
Order By: Relevance
“…Although previous studies have also shown that esmolol blunted the hypertension and tachycardia associated with several perioperative pain stimuli, including intubation, [17][18][19][20] emergence and extubation, 2 1 Mean arterial blood pressure changes following saline (n=9), esmolol low (n=7) and esmolol high (n=9) in rats subjected to formalin injection. Data are expressed as actual changes from ST (mean ± SEM).…”
Section: Discussionmentioning
confidence: 88%
“…Although previous studies have also shown that esmolol blunted the hypertension and tachycardia associated with several perioperative pain stimuli, including intubation, [17][18][19][20] emergence and extubation, 2 1 Mean arterial blood pressure changes following saline (n=9), esmolol low (n=7) and esmolol high (n=9) in rats subjected to formalin injection. Data are expressed as actual changes from ST (mean ± SEM).…”
Section: Discussionmentioning
confidence: 88%
“…Several investigators have also documented that it controls hemodynamic changes in clinical situations. [4][5][6] Another ultra-short acting beta blocker, landiolol…”
Section: Laboratory Investigationsmentioning
confidence: 99%
“…Recent knock-out mouse studies suggested that specific beta 1 -adrenergic receptor blockade, and not beta 2 Each value is mean ± SD. a = obtained just before treatment; b = obtained 30 min after saline or milrinone treatment; SBP = systolic blood pressure; MBP = mean blood pressure; DBP = diastolic blood pressure; HR = heart rate; CVP = central venous pressure; MPAP = mean pulmonary artery pressure; PAOP = pulmonary artery occlusion pressure; CO = cardiac output; SVR = systemic vascular resistance; PVR = pulmonary vascular resistance.…”
Section: Me Et Th Ho Od Ds Smentioning
confidence: 99%
“…1 ETA-ADRENERGIC receptor blockers have been used widely in the treatment of tachycardia and dysrhythmias. 1,2 Recent reports [3][4][5][6] demonstrated that the prophylactic administration of beta-adrenergic blockers in patients with ischemic heart disease reduced the incidence of postoperative ischemic events and reduced mortality.…”
mentioning
confidence: 99%